Bruner's Theory Model Approach to Class I Student Learning Outcomes at SD Negeri 56 North Bengkulu - Sinem Sinem (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Classroom Action Research is executed by subyek 11 student of class I SDN 56 Bengkulu Utara school year 2016 / 2017. From use of approach of theory Jerome S. Burner in study of items mathematics operate for the quantifying of count number, result of learning 11 student people at complete cycle I reach the KKM as much 7 people or 64% and in cycle II become 10 people or 91% happened by the improvement 27%, aktifitas student at cycle I 74% and in cycle II reach 80% there is improvement 6%. Flattening - flatten the class of cycle I is 63,2 later;then in cycle II become 72,3 there is improvement of equal to 9,1. that applying of approach of theory Jerome S. Burner can improve the result learn the class student at items operate for the quantifying of count number.Keywords: Action Research, Approach Of Theory Jerome S. Burner